Aksi Nyata Mahasiswa KKN IAIN Palangka Raya: Membenahi Infrastruktur Desa Sumber Agung Melalui Pembuatan Plang Nama Jalan - Siti Aisyah; Ahmad Riyadi; Kartika Saritilawah Rahmah; Anissa Putri Kamila; Ahmad Adi Reksi; Ahmad Jumansyah; Eka Suriansyah (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Real Work Lecture (KKN) activities carried out by IAIN Palangka Raya students in Sumber Agung Village to improve village infrastructure through making and installing road signs. This program was motivated by observations which showed that many road signs were damaged or missing, which made navigation difficult for the public and visitors. By involving seven students, this activity not only improves regional accessibility and orientation, but also strengthens collaboration between students and the community. Implementation of this program involves coordination with village officials, site surveys, and fundraising, as well as receiving active support from village residents. It is hoped that with the new road signs, it will be easier for the community to carry out activities and recognize important locations in the village, as well as increase the sense of togetherness in efforts to advance the infrastructure of Sumber Agung Village.